The Influence of Helium- Neon Laser on Methicillin – Resistant Staphylococcus aureus using Photosensitizer(TBO) (Journal of the College of Basic Education, 2022)
The main objective of this study is to determine whether the use of He-Ne laser 632.8 nm, 7.5mW in combination with toluidine blue O (TBO) is an effective tool to eradicate MRSA, and the effect of laser light on the antibiotics sensitivity in vitro.Ten isolates were methicillin-resistant Staphylococcus aureus, after testing for their sensitivity to oxacillin 6µg/ml screening test and cefoxitin 30µg antibiotic disk